Chemical concentration of major metal and rare reath elements (REE) in manganese nodules - Elderfield, Henry; Hawkesworth, Chris J; Greaves, Mervyn; Calvert, Stephen E (PANGAEA, 2022)
Oceanic manganese nodules samples were obtained from the Scripps Institution of Oceanography. They were subsamples of the powdered material used for studies of the major and minor element geochemistry of the deposits by Clavert and Price, 1977 (see Related to: reference). The powdered samples were leached with 0.1 M HCl at a ratio of 1:4 by weight at room temperature for 140 days after which the leachate and the residue were separately analyzed. The determinations of Fe, Mn, (atomic absorption spectrophotometry) and P (colorimetry) were made on the leachate. The REE were analysed by mixed-solvent ion exchange and mass spectrometric isotope dilution. Isotope analyses were performed on an A.E.I. MS5 mass spectrometer. RMS precision were generally 2% (and often 1%). except for La (5%). Eight replicate analyses of USGS standard rock BCR-1 wre used for comparison.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment